2012
DOI: 10.1016/j.envpol.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Observation of increases in emission from modern vehicles over time in Hong Kong using remote sensing

Abstract: In this study on-road gaseous emissions of vehicles are investigated using remote sensing measurements collected over three different periods. The results show that a high percentage of gaseous pollutants were emitted from a small percentage of vehicles. Liquified Petroleum Gas (LPG) vehicles generally have higher gaseous emissions compared to other vehicles, particularly among higher-emitting vehicles. Vehicles with high vehicle specific power (VSP) tend to have lower CO and HC emissions while petrol and LPG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Chan et al used remote sensing to develop CO, HC and NO emission factors for gasoline (Chan et al, 2004), diesel (Chan and Ning, 2005) and liquefied petroleum gas (LPG) (Ning and Chan, 2007) vehicles. Lau et al (2012) used remote sensing to monitor the vehicle emission trends in Hong Kong. It was found that CO, HC and NO emissions [g/km] of gasoline and LPG vehicles were continuously decreasing over the period of 1999, while CO and NO emissions of diesel vehicles increased during 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al used remote sensing to develop CO, HC and NO emission factors for gasoline (Chan et al, 2004), diesel (Chan and Ning, 2005) and liquefied petroleum gas (LPG) (Ning and Chan, 2007) vehicles. Lau et al (2012) used remote sensing to monitor the vehicle emission trends in Hong Kong. It was found that CO, HC and NO emissions [g/km] of gasoline and LPG vehicles were continuously decreasing over the period of 1999, while CO and NO emissions of diesel vehicles increased during 2004.…”
Section: Introductionmentioning
confidence: 99%
“…On-road remote sensing measurements of gas-phase emissions showed that gasoline vehicles had higher CO and HC emissions and lower NO emissions compared to diesel vehicles, while LPG vehicles overall emitted more gaseous pollutants than their light-duty petrol-and diesel-powered vehicle counterparts (Lau et al, 2012). The higher LPG vehicle emission factors were attributed to the higher usage rate of mostly LPG-powered taxis and light buses combined with insufficient vehicle maintenance, implying a gap between tightened regulations and effectiveness in the reduction of on-road emissions.…”
Section: Background Of Vehicle Emission Studies In Hong Kongmentioning
confidence: 99%
“…Sensing data was combined to obtain underlying surface feature information in Shanghai, and they used infrared gas analyzer to monitor CO 2 concentration belt transect on the ground(Pan et al, 2015) [11] . Remote sensing was used to study exhaust gas emission of vehicles, and the result showed that gasoline cars discharge more CO and HC but less NO than diesel vehicles(Jason et al, 2012) [12] . Vehicle-mounted test means obtaining the instantaneous conditions of the vehicle of the corresponding actual working conditions when running by emission analytical instrument, running state recorder and other relative equipment that are installed in the vehicle.…”
Section: Domestic and Foreign Research Situationsmentioning
confidence: 99%